Evaluation of Cardiac Performance after Treatment with the Biofield Energy Treated Proprietary Test Formulation on L-NAME and High Fat Diet-Induced Cardiovascular Disorders in Sprague Dawley Rats - Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Snehasis, Jana (Journal of Hypertension and Cardiology, 2021)
Study was aimed to evaluate effect of Biofield Treated Proprietary Formulation and Biofield Treatment per se on cardiac performance on NG-nitro-L-arginine methyl ester hydrochloride (L-NAME) and high fat diet (HFD)-induced cardiovascular disorders in Sprague Dawley rats. Nine groups were assigned, in which four were preventive maintenance groups. The constituents of test formulation were divided into two parts; one section was defined as the untreated test formulation, while the other portion of the test formulation and three groups of animals received Biofield Energy Healing Treatment remotely for about 3 minutes by a renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi. Systolic blood pressure (SBP) was significantly (p≤0.001) decreased by 13.39%, 14.65%, 17.74%, 14.36%, and 14.69% in the G5, G6, G7, G8, and G9 groups, respectively as compared to disease control (G2) group. Diastolic blood pressure (DBP)was significantly (p≤0.001) reduced by 25.95%, 24.41%, 30.79%, 24.67%, and 25.23% in G5, G6, G7, G8, and G9 groups, respectively than G2. Heart rate (HR) was significantly (p≤0.05) reduced by 6.58%, 8.06%, and 6.99% in G7, G8, and G9 groups, respectively than G2. Total leucocyte count (TLC) count was increased by 12.8% and 17.45% in G5 and G8 groups, respectively than G2 group. Neutrophils and lymphocytes were increased by 60.11% (G8) and 11.49% (G5), respectively than G2. Eosinophils were reduced by 11.11%, 20%, and 15% in G6, G7, and G9 groups, respectively than G2. Total cholesterol was significantly decreased by 22.64% (p≤0.05), 15.78%, 25.56% (p≤0.05), 22.56%, and 34.27% in G5, G6, G7, G8, and G9 groups, respectively than G2. Triglyceride was significantly (p≤0.001) reduced by 34.55%, 43.29%, 55.23%, 28.57%, and 37.28% in G5, G6, G7, G8, and G9 groups, respectively than G2. VLDL level was also significantly (p≤0.001) reduced by 80.81%, 83.61%, 86.82%, 79.19%, and 81.63% in G5, G6, G7, G8, and G9 group, respectively; while LDL was reduced by 20.32% (G9) group than G2. Atherogenic index (AI) was significantly (p≤0.001) decreased by 78.36%, 83.21%, 84.68%, 74.06%, and 72.98% in the G5, G6, G7, G8, and G9 groups, respectively than G2. The level of uric acid (UA) was significantly (p≤0.001) decreased by 57.51%, 52.36%, 45.49%, 43.78%, and 40.77% in the G5, G6, G7, G8, and G9 groups respectively, as compared with the G2 group. Serum glutamate pyruvate transaminases (SGPT) was significantly (p≤0.001) decreased by 45.96%, 48.01%, 37.19%, 37.69%, and 42.93% in the G5, G6, G7, G8, and G9 groups, respectively than G2. Creatine kinase myocardial band (CK-MB) level was significantly reduced by 10.19%, 21.97% (p≤0.01), 10.47%, and 16.94% in the G5, G6, G7, and G9 groups, than G2. Overall, the data suggested significance improvement of heart-related hematology, hepatic, and lipid parameters with respect to various pathological conditions that might be beneficial various types of cardiovascular disorders. Therefore, the results showed the significant slowdown the cardiovascular disease progression and its complications/symptoms in the preventive treatment groups viz. G6, G7, G8, and G9.
Keywords: Biofield Treatment; The Trivedi Effect®; High Fat Diet; Cardiovascular Disorders; Atherogenic index; Lipid profile; hematology; CKMB